Comparison of the paper‐based and electronic versions of the Dermatology Life Quality Index: evidence of equivalence. (1st November 2017) - Ali, F.M.; Johns, N.; Finlay, A.Y.; Salek, M.S.; Piguet, V.
Summary: Background: The use of patient‐reported outcome measures in electronic format has been increasing. However, these formats are usually not validated or compared with the original paper‐based formats, so there is no evidence that they are completed in the same way. Objectives: To compare the conventional paper version with a web‐based application (iPad ® ) version of the Dermatology Life Quality Index (DLQI) to assess equivalence of scores. Methods: The study employed a randomized crossover design using a within‐subjects comparison of the two formats of the questionnaire. International Society for Pharmacoeconomics and Outcomes Research (ISPOR) guidelines were followed. Participants aged over 18 years with any confirmed skin condition were recruited from a teaching hospital dermatology outpatient clinic. Expected intraclass correlation coefficient (ICC) was 0·9 (α = 0·05). Results: A total of 104 patients were recruited, median age 53·5 years (interquartile range 37·3–67·8; 43% male). The ICC showed high concordance between the total DLQI scores from paper and iPad versions (ICC 0·98; 95% confidence interval 0·97–0·99). Patients took a median of 78 s to complete the electronic version and 73 s for paper ( P = 0·008): 76% preferred the electronic version and perceived completion to take a shorter time. Conclusions: There is high concordance and thus equivalence between the iPad and paper versions of the DLQI, with an ICC of 0·98, and a clear patient preference for the iPad version.